A prehospital paediatric tension viscerothorax presenting as a tension pneumothorax: a diagnostic dilemma. Issue 11 (2nd August 2010) - Jones, Chris; Tzannes, Alex; Reid, Cliff
Abstract : This article reports a case of a paediatric pre–hospital tension viscerothorax, and it subsequent management. It also dicusses the difficulty in diagnosing this condition in the pre-hospital arena.